Evaluation of brain plasticity in patients with hypoglossal-facial nerve transfer: analysis of 70 cases - RANC, Revista Argentina de Neurocirugia; Bourguet, Martín Emilio; Biancardi, Mauro; Badilla Campos, Tomás Alfonso; Minghinelli, Federico Eduardo; Iglesias, Brenda; Socolovsky, Mariano (Revista Argentina de Neurocirugía, 2024)
Background: brain plasticity is crucial for regaining independent volitional control of facial muscles following hypoglossal-facial (HF) anastomosis, ensuring that tongue movements do not induce synchronous facial movements.Objective: to evaluate brain plasticity using the Plasticity Grading Scale (PGS).Methods: seventy patients were evaluated after an HF anastomosis: 1) using the donor nerve program, i.e., moving the tongue, and 2) activating the mimic muscle, consciously avoiding the use of the donor nerve. A 4-point Plasticity Grading Scale (PGS) was used to assess voluntary control.Results: 29 achieved a PGS of 1; 37 a PGS of 2; 4 a PGS of 3, and none reached a PGS of 4. A significant negative relationship (p
Keywords: Facial Paralysis; Hypoglossal; Peripheral nerves; Plasticity